Penerapan Metode Pembelajaran Kooperatif “Think Pair Share” Dalam Mata Kuliah Kimia Dasar Di Jurusan Farmasi Universitas Qamarul Huda Badaruddin - Pomeistia, Meilynda (YAYASAN HAMJAH DIHA bekerjasama dengan PENA INSTITUTE, 2025)
This research to describe the implementation of the cooperative learning model Think Pair Share (TPS) in enhancing student engagement in the General Chemistry course at the Pharmacy Department of Universitas Qamarul Huda Badaruddin. The background of this research lies in the low level of active participation among students during learning activities, as well as the lack of deep conceptual understanding of chemistry, which is often caused by the dominance of lecture-based methods. The TPS method is applied through three stages: individual thinking (think), paired discussion (pair), and sharing the discussion results with the class (share). This research employs a descriptive qualitative approach, with data collected through observation techniques. The findings indicate that the TPS model can increase students’ active involvement in discussions, strengthen their understanding of basic chemistry concepts, and create a more interactive and collaborative learning atmosphere. Therefore, TPS is recommended as an effective alternative learning strategy for conceptually and analytically oriented courses such as General Chemistry.